Untargeted metabolomic and lipidomic analyses reveal lipid dysregulation in the plasma of acute leukemia patients - Arévalo, Cindy; Rojas, Laura; Santamaria, Mary; Molina, Luisana; Arbeláez, Lina; Sánchez, Paula; Ballesteros-Ramírez, Ricardo; Arevalo-Zambrano, Monica; Quijano, Sandra; Cala, Mónica P.; Fiorentino, Susana (Frontiers in Molecular Biosciences, 2023)
Acute leukemias (AL) are aggressive neoplasms with high mortality rates. Metabolomics and oxidative status have emerged as important tools to identify new biomarkers with clinical utility. To identify the metabolic differences between healthy individuals (HI) and patients with AL, a multiplatform untargeted metabolomic and lipidomic approach was conducted using liquid and gas chromatography coupled with quadrupole-time-of-flight mass spectrometry (LC-QTOF-MS or GC-QTOF-MS). Additionally, the total antioxidant capacity (TAC) was measured. A total of 20 peripheral blood plasma samples were obtained from patients with AL and 18 samples from HI. Our analysis revealed 135 differentially altered metabolites in the patients belonging to 12 chemical classes; likewise, the metabolic pathways of glycerolipids and sphingolipids were the most affected in the patients. A decrease in the TAC of the patients with respect to the HI was evident. This study conducted with a cohort of Colombian patients is consistent with observations from other research studies that suggest dysregulation of lipid compounds. Furthermore, metabolic differences between patients and HI appear to be independent of lifestyle, race, or geographic location, providing valuable information for future advancements in understanding the disease and developing more global therapies.